Investigation of Icelandic Dust Presence in the Aerosols Collected at Hornsund (Svalbard, Norwegian Arctic) in Spring 2019 - Moroni, Beatrice; Crocchianti, Stefano; Nawrot, Adam; Dagsson Waldhauserova, Pavla; Cappelletti, David (Atmosphere, 2024)
An integrated morphological and chemical analysis of Arctic aerosols was undertaken for Icelandic dust and Svalbard aerosols to be compared by scanning electron microscopy coupled with EDS microanalysis (SEM-EDS) via imaging and chemical analysis techniques. Results of the characterization of the particles from both surface sediments and suspended dust from desert areas in Iceland confirmed that volcanic glass is an excellent marker of Icelandic dust origin. Classification diagrams of particle chemical composition clearly distinguished the volcanic glass particles from the local surface sediments at Hornsund, Svalbard. In the same diagrams, a few particles were found in the aerosols from Hornsund which were morphologically and chemically similar to the Icelandic volcanic glass particles. Such properties, in principle, cannot be considered exclusive to volcanic glass. However, since Iceland is the largest and the most active source of long-range transported dust in the northern European high latitudes, and air mass trajectories reaching Hornsund did, actually, pass Iceland before the aerosol collection in the period under consideration, these particles likely originated in Iceland. On the other hand, the comparison with local and Icelandic sediments revealed the presence in the aerosols from Hornsund of particle types that cannot be attributed to either local or Icelandic dust. This observation highlights the possibility of extending and validating the application of the proposed geochemical criterion to different dust sources across the Arctic and the sub-Arctic, provided a consistent geochemical databank of representative dust sources from these areas is arranged.